Heckscher-Ohlin theory when countries have different technologies - Eric O'N. Fisher (Center for Economic Studies and ifo Institute (CESifo), 2010)
Rethinking the foundations of Heckscher-Ohlin theory when countries have different technologies, this paper shows how to make the proper adjustments for international productivity differences. The central tool is a factor conversion matrix that computes the local factor content of foreign Rybczynski effects. Factor-specific productivities are a special case of these more general linear relationships.
Keywords: F10; O47; 330; Faktorproportionentheorem; Produktionsfaktor; Technologie; Produktivität; Branchenentwicklung; Theorie